Polishing effect on the physicochemical properties of porang flour using centrifugal grinder. Issue 1 (April 2020) - Witoyo, J E; Ni'maturohmah, E; Argo, B D; Yuwono, S S; Widjanarko, S B
Abstract: Porang tubers are an agricultural product from one of the endemic plants in Southeast and East Asia, which found in the Indonesian forest and is a vital source of glucomannan. The simple processing of porang tubers is made into chips, ground using mechanical milling followed by air fractionation. However, porang flour from mechanical milling still has high impurities, such as calcium oxalate more than 2% and not safe for human consumption. The polishing process using a centrifugal grinder is needed to remove impurities that still attached to the glucomannan cells by the friction principle. The purpose of this study was to investigate the effect of the polishing cycle on physicochemical properties of porang flour. The experimental design used polishing historical data and process was conducted in two replication. The results showed the polishing cycle had a significant effect (p < 0.05) on the glucomannan content, viscosity, degree of whiteness, calcium oxalate content, starch content, protein content, and fat content. The best of polished porang flour was obtained on the 5 times of polishing cycle based on multiple attributes calculations.